Antibacterial Activity of Seaweed (Gracilaria species) Extracts Against Infectious Pathogens - P., Prasad M.; Sushant, Shekhar; Ganesh, Rindhe (Asian Journal of Biological and Life Sciences, 2012)
Pathogenic microorganisms currently resistant to drugs cause innumerable mortality in human population which creates need for searching new antibacterial agents from easily available unexplored natural sources such as seaweed. In this study the antibacterial activity of seaweeds (Gracilaria verrucosa, Gracilaria foliifera, Gracilaria corticata, Gracilaria crassa and Gracilaria edulis) was tested against human bacterial pathogens (K. pneumoniae, P. aeruginosa, E. aerogenes, S. typhi and S. aureus). Different types of extracts (Acetone, Benzene, Butanol, Chloroform, Ethanol, Ethyl Acetate, Hexane, Isoamyl Alcohol, Methanol, and Propanol) were evaluated for antibacterial activity by agar cut well diffusion methods. All the studied species of Gracilaria showed antibacterial activity. The best results were obtained by isoamyl extract with inhibition activity on most of the pathogens and G. verrucosa is slightly more effective compared to other Gracilaria species. The isoamyl alcohol extract showed highest (24 mm) zone of inhibition followed by Chloroform extract with highest zone of inhibition (21 mm). These results show the potential of Gracilaria species for screening new bioactive (antibacterial) compounds.